Impact of the complex humanitarian crisis on the epidemiology of the cardiometabolic risk factors in Venezuela - González-Rivas, Juan P; Mechanick, Jeffrey I; Ponte, Carlos; de Oliveira-Gomes, Diana; Iglesias-Fortes, Rocio; Machado, Livia; Duran, Maritza; Marulanda, Maria Inés; Nieto-Martínez, Ramfis (Clinica e investigacion en arteriosclerosis, 2022)
BACKGROUND: The complex humanitarian crisis (CHC) in Venezuela is characterized by food insecurity, hyperinflation, insufficient basic services, and the collapse of the healthcare system. The evolution of the epidemiology of cardiometabolic risk factors in this context is unknown. AIM: To compile the last 20 years evidence on the prevalence of cardiometabolic risk factors in adults of Venezuela in the context of the CHC. METHODS: A comprehensive literature review of population-based studies of adults in Venezuela from 2000 to 2020. RESULTS: Seven studies (National EVESCAM 2014-2017, 3 regions VEMSOLS 2006-2010, Maracaibo city 2007-2010, Merida city 2015, Mucuchies city 2009, Barquisimeto city CARMELA 2003-2005, and Zulia state 1999-2001) with samples sizes ranging from 109 to 3414 subjects were included. Over time, apparent decrease was observed in smoking from 21.8% (2003-2005) to 11.7% (2014-2017) and for obesity from 33.3% (2007-2010) to 24.6% (2014-2017). In contrast, there was an apparent increase in diabetes from 6% (2003-2005) to 12.3% (2014-2017), prediabetes 14.6% (2006-2010) to 34.9% (2014-2017), and hypertension 24.7% (2003-2005) to 34.1% (2014-2017). The most prevalent dyslipidemia - a low HDL-cholesterol - remained between 65.3% (1999-2001) and 63.2% (2014-2017). From 2006-2010 to 2014-2017, the high total cholesterol (22.2% vs 19.8%, respectively) and high LDL-cholesterol (23.3% vs 20.5%, respectively) remained similar, but high triglycerides decreased (39.7% vs 22.7%, respectively). Using the same definition across all the studies, metabolic syndrome prevalence increased from 35.6% (2006-2010) to 47.6% (2014-2017). Insufficient physical activity remained steady from 2007-2010 (34.3%) to 2014-2017 (35.2%). CONCLUSION: Changes in the prevalence of cardiometabolic risk factors in Venezuela are heterogeneous and can be affected by various social determinants of health. Though the Venezuelan healthcare system has not successfully adapted, the dynamics and repercussions of the CHC on population-based cardiometabolic care can be instructive for other at-risk populations.
Keywords: Public health; Hyperlipidemias; Prevalence; Cardiometabolic Risk Factors; Metabolic Syndrome; Venezuela; prevalence; Adult; Cardiometabolic risk factors; Cholesterol; Factores de riesgo cardiometabólico; hyperlipidemie; Salud pública; metabolický syndrom; Humans; kardiometabolické riziko; rizikové faktory; Epidemiología; dospělí; Risk Factors; Epidemiology; lidé; cholesterol